Contação de histórias como linguagem artística e prática pedagógica em sala de aula - Silva, Elaine Camargos da (2020)
This article refers to the professional master's research carried out with children inserted in a common literacy room, from the 2nd year of elementary school, in a school in the Municipal Education Network of Uberlândia, during 2019. Due to the fact that I have been working as a regent teacher, Literature, and Language teacher for many years, with an emphasis on storytelling, I observed, during pedagogical practices, the importance of artistic language as a fundamental element when telling stories. As children's literature is an instigator, provoking meaningful learning in the classroom, I focused on it as an artistic language in the teacher's pedagogical practice. For this research, I started with a theoretical study, in dialogue with several authors and reference materials, which offered support during the pedagogical action. As a guideline, there was the time to tell stories and pedagogical practice involving children and teacher, in interface with artistic language in the area of scenic art, visual art and music. They are fundamental artistic languages for the development of skills, such as: imagination, creativity, playfulness, autonomy. They are often overlooked or little valued in the school context, and storytelling is a pedagogical practice that will provide the development of these skills in a pleasant and playful way.